Physiotherapy of rheumatoid hand improves hand functions without any change on periarticular bone mineral density - Ozgocmen, S.; Akgun, M.; Kaya, A.; Ardicoglu, O. (B M J Publishing Group, 2006)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR 2006) -- JUN 21-24, 2006 -- Amsterdam, NETHERLANDS